Cartilage Delamination Flap Mimicking a Torn Medial Meniscus - Gan Zhi-Wei Jonathan; Hamid Rahmatullah Bin Abd Razak; Mitra Amit Kanta (Case Reports in Orthopedics)
We report a case of a chondral delamination lesion due to medial parapatellar plica friction syndrome involving the medial femoral condyle. This mimicked a torn medial meniscus in clinical and radiological presentation. Arthroscopy revealed a chondral delamination flap, which was debrided. Diagnosis of chondral lesions in the knee can be challenging. Clinical examination and MRI have good accuracy for diagnosis and should be used in tandem. Early diagnosis and treatment of chondral lesions are important to prevent progression to early osteoarthritis.